Training for the bike to run transition in triathlon - Haworth, J.; Walsh, M.; Strang, A.; Hohl, J.; Spraets, S.; Wilson, M.; Brown, C. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
The purpose of this study was to examine the effect of a practice regimen that targets the bike-to-run transition for triathlons; known as brick workouts. The principle of specificity suggests that since this skill is a critical transition in a triathlon, having further impact on the subsequent running section, practicing this skill is vital for success. Moreover, the identification of performance parameters that quantify a successful transition will serve to maximize practice efficiency. Subjects (N=12) performed either brick workouts or single event training, to examine their effects on the bike-run transition. Our results indicate that the brick workouts had a positive effect by eliciting an increased adaptability in knee behavior in response to the transition from cycling to running. Quicker adoption of efficient running mechanics may ensue, leading to less fatigue and greater performance.